2017
DOI: 10.1242/dev.146613
|View full text |Cite
|
Sign up to set email alerts
|

A framework for understanding the roles of miRNAs in animal development

Abstract: MicroRNAs (miRNAs) contribute to the progressive changes in gene expression that occur during development. The combined loss of all miRNAs results in embryonic lethality in all animals analyzed, illustrating the crucial role that miRNAs play collectively. However, although the loss of some individual miRNAs also results in severe developmental defects, the roles of many other miRNAs have been challenging to uncover. This has been mostly attributed to their proposed function as tuners of gene expression or prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 133 publications
5
115
0
1
Order By: Relevance
“…MiRNAs as small noncoding RNAs have key roles in the various cellular processes through the regulation of gene expression and RNA silencing (Alberti & Cochella, 2017). These RNAs can be found in two type of pre-miRNAs and mature miRNAs, and it is the | 10721 mature form that mediated their biological roles (Peng & Croce, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs as small noncoding RNAs have key roles in the various cellular processes through the regulation of gene expression and RNA silencing (Alberti & Cochella, 2017). These RNAs can be found in two type of pre-miRNAs and mature miRNAs, and it is the | 10721 mature form that mediated their biological roles (Peng & Croce, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as Ebert and Sharp (as well as Caviglia et al) have suggested, the function of miRNAs may be mainly to contribute to robustness in biological processes, rather than to control biological processes as primary regulators. Alberti et al also pointed out the moderate regulatory effects of miRNAs on gene expression, given that deletion of a wide range of specific miRNAs seldom causes major defects in the overall organism. They classified miRNAs into two categories: “core miRNAs” and “periphery miRNAs.” The core miRNAs are involved in the early stage of cellular differentiation, and their loss can cause lethal effects on the whole organism.…”
Section: In Vivo Preclinical Studies Showing Mir‐21 Profibrotic Effectsmentioning
confidence: 99%
“…Genetic, biochemical and computational studies have identified hundreds of miRNAs in humans with diverse and often conserved functions affecting most developmental process (1,2). Accordingly, mice with defects in the miRNA biogenesis pathway die during embryonic development (3)(4)(5). Loss-of-function of individual miRNAs leads to diverse phenotypes in various organ systems, reflecting the limited expression of many miRNAs during specific stages of development or in distinct cell types (1).…”
Section: Introductionmentioning
confidence: 99%